Type C Personality: Conceptual Refinement and Preliminary Operationalization - Rymarczyk, Karolina; Turbacz, Anna; Strus, Włodzimierz; Cieciuch, Jan (Frontiers in Psychology, 2020)
In the paper we have presented our proposal for a reconceptualization and operationalization of Type C (cancer-prone) personality. Based on theoretical analyses, taking account of both the literature on Type C and models of personality structure, we have proposed a two-facet structure of Type C, comprising Submissiveness (the interpersonal aspect) and Restricted Affectivity (the intrapersonal aspect). The study devoted to the validation of the measure of Type C involved 232 participants aged 18 to 70 (M = 29.35, SD = 8.93; 54% male). We used (a) our proposed measure of Type C personality and (b) the Circumplex of Personality Metatraits Questionnaire (CPM-Q-SF; Strus and Cieciuch, 2017), assessing personality metatraits. The measure of Type C proved to have acceptable internal consistency (Cronbach’s alpha was .85 for Submissiveness and .78 for Restricted Affectivity). The measurement model in confirmatory factor analysis with two latent variables proved to be well fitted to the data. We have also confirmed the hypothesis concerning the location of the two facets of Type C personality close to each other in the theoretically predicted area between the Delta-Plus/Self-Restraint and Beta-Minus/Passiveness metatraits (in the Circumplex of Personality Metatraits). The clinical value of the theoretically refined Type C can be tested in the next step in research on patients with cancer.